Baseline ALBI score and early variation of serum AFP predicts outcomes in patients with HCC treated by atezolizumab–bevacizumab. (14th December 2022) - Campani, Claudia; Bamba‐Funck, Jessica; Campion, Bertille; Sidali, Sabrina; Blaise, Lorraine; Ganne‐Carrié, Nathalie; Demory, Alix; Sutter, Olivier; Larrey, Edouard; Evain, Manon; Ghannouchi, Haroun; Wagner, Mathilde; et al.
Abstract: Background: The combination of atezolizumab and bevacizumab (AtezoBev) is the current first‐line treatment for patients with hepatocellular carcinoma (HCC). Our aim was to evaluate the prognostic role of alpha‐foetoprotein (AFP) early response and its combination with albumin–bilirubin (ALBI) in these patients. Methods: Patients with HCC under AtezoBev with AFP > 20 ng/ml were included in three centres. The optimal threshold of AFP variation after 3 weeks of treatment was identified for overall survival (OS) and radiological response (RR) using RECIST 1.1 and mRECIST and its ability to predict progression‐free survival (PFS) and OS was tested using univariate and multivariate analysis in derivation and validation cohorts. Results: Seventy‐five patients with AFP values >20 ng/ml were included. Fifty‐eight patients were male with a median age of 63.5 years; 73% had cirrhosis and HCC stage was classified as BCLC B (18.7%) or C (81.3%). In the derivation cohort ( n = 38), a decline in AFP ≥ 20% at 3 weeks (AFP early response) was associated with RR using mRECIST criteria (OR: 13.09 95% CI: 1.44–19.34 p = .02), PFS (HR: 0.42; 95% CI: 0.19–0.93, p = .03) and OS (HR: 0.35; 95% CI: 0.15–0.83, p = .01). AFP early response was confirmed as predictor of RR ( p = .02 for mRECIST) and OS ( p = .03) in the validation cohort ( n = 37). In the whole cohort, the combination of ALBI and AFP early response was significantly associated with OS ( p = .046) and PFS ( p = .012) with a poor prognosis in patients belonging to the ALBI2‐AFP non‐responders class. Conclusion: AFP early response at 3 weeks predicts oncological outcomes in HCC patients treated with AtezoBev and combination with ALBI grade refines prognostic discrimination.